Influência da relação C:N:P no desempenho de reatores tipo UASB - Gabardo, Renan Artur (2016)
Wastewater treatment using Anaerobic reactors, such as Up-flow Anaerobic Sludge Blanket – known as UASB, has been utilized for several years in some regions of Brazil. For design criteria and process control, it is considered several parameters as temperature, substrate pH, hydraulic load and nutrient ratio. Wastewater treatment plants process effluents with a variety of nutrient ratios and there is no consensus about what would be the optimal ranges for operating those reactors. Aiming to understand and assist the design, dimensioning and control of these reactors, this work evaluated the influence of the ratios of major nutrients (carbon, nitrogen and phosphorus) in the performance of a UASB reactor treating synthetic effluent. This work has used four UASB reactors with same characteristics, besides that, conditions such as HRT, organic load and temperature were the same among reactors, the only condition varying was C:N:P affluent ratios. The synthetic affluent produced had a COD expected of 500 mg/L, value similar to domestic wastewater. The analyses were divided in two parts: monitoring lasting 362 days and three profiles of 10 hours each. During monitoring were realized analyses of COD, alkalinity, volatile fatty acids, methane production, besides temperature and pH. Profiles analysed COD, phosphate and ammoniacal nitrogen. For the results discussion were realized statistical tests in order to find a correlation between affluents C:N:P ratios and results of COD removal, production and consumption of alkalinity and volatile fatty acids, and methane production rates. It was only found correlation between methane production and C:N:P ratios tested; for the other analyses no correlation was confirmed. All reactors obtained high COD removal rates - above 75 percent, this probably happened because synthetic affluent source of carbon was glycose; production of alkalinity and consume of volatile fatty acids among the reactors were similar, indicating an effective functioning. Regarding methane production, the reactor that operated with expected ratio of 300:5:1 obtained a performance 40% higher than the others, reaching a daily average of 162,05 mLCH4/gDQO.